Lanzamiento de nuevas marcas en industrias de productos homogéneos básicos con altos niveles de concentración (2007)
This work applies the models of Cournot and Stackelberg to a homogenous product industry with high level of concentration. The object is to use these models as decision criterion over the alternative to introduce a new mark by incumbent not leader. It is wanted to establish if to send a new mark it would be a good strategy for a firm in the search to catch greater market. It is assumed that in a market of basic and homogenous goods, the demand is not modified before the entrance of a new mark and that the market space that absorbs the new mark comes from the participation that reduces of the existing marks. The results indicate that the amount that produces each competitor again converges with the balance of Cournot, thus, does not exist additional benefit product of the launching of the new mark, if rationality assumes. Theoretically the firms with better position in the market will be seen less inclined send new marks and will prefer to maintain or to improve their positioning, the companies with less participation in the market will be most inclined to make new launchings. The conclusion is the introduction of marks in homogenous markets of basic goods little differentiated is not an interesting strategy to increase the participation in the market when the marks of those who send products are not well positioned. The mill industry of white rice on Colombia was used for illustration of conclusions.